Environmental conditions of gully erosion in Hungary - Kertész, Ádám (Hungarian Geographical Bulletin, 2009)
Soil erosion research has become very important over the last decades. It is the subject matter of several disciplines, geographers, geomorphologists, soil scientists, hydrologists, agronomists and other scientists publish on this topic and the authors of these publications are members of interdisciplinary and in most cases also international teams. Research on soil erosion by water concentrated, however, mainly on sheet erosion. The role of gully erosion has been recognized only lately. The presence and dynamics of various gully types (permanent, ephemeral and bank gullies) can be observed and their development can be followed under different climatic conditions and various land use types and sheet and rill erosion measurements on runoff plots are not realistic indicators of total catchment erosion (Poesen, J. et al. 2003). Another weakness of plot measurements of sheet erosion is that they do not give information about the redistribution of eroded soil within a field (Poesen, J. et al. 2003). Gully erosion plays a decisive role in the redistribution of eroded soil on a slope and in delivering it to watercourses (Evans, R. 1993, cited by Poesen, J. et al. 2003). All these statements point to the need of intensive research on gully erosion.